2013
DOI: 10.1155/2013/264832
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Catalyst Activity of WO3 Using Polypyrrole as Support for Acidic Esterification of Glycerol with Acetic Acid

Abstract: A series of polypyrrole supported WO3were fabricated and characterized by FT-IR, XRD, XPS, BET, TGA, and FESEM-EDX. The activity of the catalysts was tested in glycerol esterification with acetic acid, and it found that WO3-Ppy-20 (nanocomposite with 20% WO3loaded) showed the maximum catalyst activity with 98% and selectivity of 70% to triacetin at 110°C with a reaction duration of 10 h and also recorded the highest selectivity (75%) for acetylation of glycerol to monoacetin with about 59% conversion only. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Therefore, TAG selectivity in glycerol esterification with acetic acid is temperature dependent because only 7% of TAG was produced at temperatures below 90°C compared with 55% selectivity at 110°C. Similarly, Mufrodi et al [107] reported that increase in reaction temperature from 50°C to 110°C increased glycerol conversion from 58.8% to 98% and TAG selectivity from 5% to 70%; however, MAG selectivity decreased from 75% to 10% by using heterogeneous tungstic oxide catalyst WO 3 supported on polypyrrole (polymer material). The optimum temperature should be selected based on the material used for catalyst synthesis.…”
Section: Effects Of Reaction Temperaturementioning
confidence: 93%
See 3 more Smart Citations
“…Therefore, TAG selectivity in glycerol esterification with acetic acid is temperature dependent because only 7% of TAG was produced at temperatures below 90°C compared with 55% selectivity at 110°C. Similarly, Mufrodi et al [107] reported that increase in reaction temperature from 50°C to 110°C increased glycerol conversion from 58.8% to 98% and TAG selectivity from 5% to 70%; however, MAG selectivity decreased from 75% to 10% by using heterogeneous tungstic oxide catalyst WO 3 supported on polypyrrole (polymer material). The optimum temperature should be selected based on the material used for catalyst synthesis.…”
Section: Effects Of Reaction Temperaturementioning
confidence: 93%
“…Ghoreishi et al [107] reported a linear relationship between the increase in time and glycerol conversion rate in a 10-h reaction; they observed 70% TAG selectivity within 10 h and a corresponding reduction in MAG formation. Consequently, DAG selectivity increased from 25% to 50% within 6 h of reaction and then decreased.…”
Section: Effect Of Reaction Timementioning
confidence: 99%
See 2 more Smart Citations
“…Thus, reliable fabrication of devices using these materials by cost effective methods is a major concern of many researchers. One such method is the incorporation of metal/metal oxides into the conducting polymers via a chemical or electrochemical route [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%